Research on fatigue performance of CFRP reinforced steel crane girder. (15th October 2016) - Yue, Qing-Rui; Zheng, Yun; Chen, Xuan; Liu, Xiao-Gang
Abstract: The fatigue performance of CFRP reinforced steel crane girders was comparatively studied by experimental research. In addition, the stress concentration behavior and the stress intensity factor were also discussed to analyze the mechanism of CFRP reinforcement. The research confirmed that the reinforcement using CFRP layers can significantly improve the fatigue life of the girder, especially if the fatigue stress amplitude is not too large. It is suggested to arrange U-shaped hoop with over 3 layers at the end of the longitude layers, and aside the stiffeners at midspan. The longitude CFRP layers should fully cover the side faces of the bottom flange to avoid potential fatigue fraction initiation here. Fisher's provision will significantly underestimate the fatigue life of CFRP reinforced girders because it cannot consider the stress concentration relief aside the stiffeners. The CFRP layers can perfectly restrain the development of fatigue fracture. Thus, the stress intensity factor of CFRP reinforced girders increases much slower with fracture length in comparison with unreinforced girders, especially after the fracture develops into the flange. The increasing of longitude CFRP layers may just give little decrease of the stress intensity factor, but lower fatigue stress amplitude can significantly decrease the stress intensity factor.